The stellar halo of isolated central galaxies in the Hyper Suprime-Cam imaging survey. Issue 2 (16th May 2019) - Wang, Wenting; Han, Jiaxin; Sonnenfeld, Alessandro; Yasuda, Naoki; Li, Xiangchong; Jing, Yipeng; More, Surhud; Price, Paul A; Lupton, Robert; Rykoff, Eli S; Stark, David V; Lan, Ting-Wen; et al.
Abstract: We study the faint stellar halo of isolated central galaxies, by stacking galaxy images in the HSC survey and accounting for the residual sky background sampled with random points. The surface brightness profiles in HSC r band are measured for a wide range of galaxy stellar masses (9.2 < log10 M ∗ /M⊙ < 11.4) and out to 120 kpc. Failing to account for the stellar halo below the noise level of individual images will lead to underestimates of the total luminosity by ≤15%. Splitting galaxies according to the concentration parameter of their light distributions, we find that the surface brightness profiles of low-concentration galaxies drop faster between 20 and 100 kpc than those of high-concentration galaxies. Albeit the large galaxy-to-galaxy scatter, we find a strong self-similarity of the stellar halo profiles. They show unified forms once the projected distance is scaled by the halo virial radius. The colour of galaxies is redder in the centre and bluer outside, with high-concentration galaxies having redder and more flattened colour profiles. There are indications of a colour minimum, beyond which the colour of the outer stellar halo turns red again. This colour minimum, however, is very sensitive to the completeness in masking satellite galaxies. We also examine the effect of the extended PSF in the measurement of the stellar halo, which is particularly important for low-mass or low-concentration galaxies. The PSF-corrected surface brightness profile can be measured down to ∼31 $mag\, arcsec^{-2}$ at 3σ significance. PSF also slightly flattens the measured colour profiles.